New scandium borates RxLayScz(BO3)4 (x+y+z=4, R=Sm, Tb): Synthesis, growth, structure and optical properties. (June 2020) - Kuznetsov, A.; Kokh, A.; Kononova, N.; Shevchenko, V.; Uralbekov, B.; Ezhov, D.; Svetlichnyi, V.; Goreiavcheva, A.; Kokh, K.
Graphical abstract: Highlights: Sm0.34 La0.68 Sc2.98 (BO3 )4 and Tb0.23 La0.77 Sc3 (BO3 )4 crystal was grown from LiBO2 flux. Sm0.34 La0.68 Sc2.98 (BO3 )4 and Tb0.23 La0.77 Sc3 (BO3 )4 structure was refinement by Rietveld method. Luminescent and absorption spectra for Sm0.34 La0.68 Sc2.98 (BO3 )4 and Tb0.23 La0.77 Sc3 (BO3 )4 were measured. SHG of powered Sm0.34 La0.68 Sc2.98 (BO3 )4 and Tb0.23 La0.77 Sc3 (BO3 )4 was comparable with KDP. Abstract: Herein we report the growth of new Rx Lay Scz (BO3 )4 (x + y+z = 4, R = Sm, Tb) crystals with large second-harmonic generation (SHG) responses. The obtained compounds, grown from eutectic LiBO2 -LiF flux by the TSSG method, crystallize in the space group P321 with the cell parameters a = 9.800(15) Å and c = 7.9565(7) Å for Sm0.34 La0.68 Sc2.98 (BO3 )4 and a = 9.7976(7) Å and c = 7.9567(12) Å for Tb0.23 La0.77 Sc3 (BO3 )4 . These crystalline materials also exhibit luminescent properties related to the optical transitions of Tb 3+ and Sm 3+ ; specifically, Tb0.23 La0.77 Sc3 (BO3 )4 shows a strong green emission that is dominated by the 5 D4 to 7 F5 transition. The studied crystals' SHG intensities were higher than those of KDP crystals, revealing their potential uses in various nonlinear optics applications.